Normative values of anthropometric characteristics and body composition in senior Croatian taekwondo competitors - Cular, D.; Bešlija, T.; Kezic, A. (Acta Kinesiologica, 2020)
The aim of this study was to determine the normative values of body composition and anthropometric characteristics of senior Croatian taekwondo competitors of both sexes, according to weight category. The subject sample consisted of 137 participants of the national senior taekwondo championships (Split, 2015). The subject sample was divided into two subsamples: male seniors (n=73) and female seniors (n=64). Nine variables were measured and according to their role, they were divided in two groups: morphological measures (body height, body mass) and variables defining body composition (body mass index, body fat (%), body fat (kg), muscle mass (kg), lean body mass (kg), total body water (kg), and basal metabolism (kJ)). The measurements were taken by the Martin anthropometer and the TANITA diagnostic measuring device, model BC 418, based on the bioimpedance principle. The obtained results -mean value, variability (SD) and the ranges of values (MIN-MAX) -are the Croatian reference values of anthropometric characteristics and body composition for male and female senior taekwondo competitors of different weight category. Apart from its direct scientific contribution to describing the characteristics of competitors in terms of their body build and composition, the importance of this study is in possible control of body mass in male and female taekwondo competitors.